Esfericidad ventricular izquierda (índice de esfericidad) en el perro - Buzzano, O.O. (2012)
Heart disease imposes adaptation phenomena which lead to the modification of the cardiac geometry. The degree of heart change from its normal form has clinical and hemodynamic significance. The more the heart tends to the spherical shape, the worse is the prognosis. The sphericity index allows a quantitative assessment of the degree of sphericity has reached the diseased heart. In this study the authors determined the normal value of the sphericity index by two techniques in 91 dogs. The value obtained for the sphericity index by dividing axes was 1.58 and for the case of division of areas of 1.45. In both cases, significant differences (p <0.05) between males and females were obtained. The sphericity index is an indicator of worsening to the heart and to prognosis, since the processes of higher incidence in canine cardiology, the endocardiosis of mitral valve and dilated cardiomyopathies, both promote volume overload that leads inexorably to left ventricular sphericity